Eliciting Societal Values About Cyberstalking Policy Decisions - Dhillon, Gurpreet (2016)
Cyberstalking is a significant challenge in the era of Internet and technology. When dealing with cyberstalking, institutions and governments alike have a problem in how to manage it and where to allocate resources. Hence, it is important to understand how individuals feel about the problem of cyberstalking so it can be managed in the context of cybersecurity. To do this the problem question is twofold: First, what objectives are important based on the values of the general public with regard to the prevention of cyberstalking. Second, what are the possible scenarios for the implementation of these objectives that organizations, governments and society at large can look to that will guide their decision making process. In this paper we utilize Keeney’s (1990) public value forum to elicit public values which can form the basis for the decision making process in preventing cyberstalking so institutions and governments can allocate resources prudently